2005
DOI: 10.1037/0735-7044.119.1.302
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure Causes Attention Deficits in Male Rats.

Abstract: Children with fetal alcohol spectrum disorder (FASD) are often diagnosed with attention-deficit/ hyperactivity disorder (ADHD). These children show increases in reaction time (RT) variability and false alarms on choice reaction time (CRT) tasks. In this study, adult rats prenatally exposed to ethanol were trained to perform a CRT task. An analysis of the distribution of RTs obtained from the CRT task found that rats with a history of prenatal ethanol exposure had more variable RT distributions, possibly becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 50 publications
(81 reference statements)
1
68
2
2
Order By: Relevance
“…Some of the literature suggests that the behavioral disturbances observed in ethanol pups are due to the direct effect of alcohol during gestation. Indeed, many studies showing an activity and/or attention disorder in a rodent model of fetal alcohol used an alcoholization protocol that does not cover the period of lactation (Hausknecht et al 2005;Mothes et al 1996;Torres and Zimmerberg 1992). However, the essential developmental steps for the brain structures involved in motor activity and attentional occur during gestation (Rice and Barone 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the literature suggests that the behavioral disturbances observed in ethanol pups are due to the direct effect of alcohol during gestation. Indeed, many studies showing an activity and/or attention disorder in a rodent model of fetal alcohol used an alcoholization protocol that does not cover the period of lactation (Hausknecht et al 2005;Mothes et al 1996;Torres and Zimmerberg 1992). However, the essential developmental steps for the brain structures involved in motor activity and attentional occur during gestation (Rice and Barone 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Brain dysfunction is a consequence of both ethanol-induced toxicity and ethanolinduced nutritional changes in pregnant females (Bartley et al 1983;Dreosti 1993;Weinberg 1984). These clinical data can be correlated with laboratory data showing that in utero alcohol exposure in rats leads to hyperactivity and/or attention deficits in the offspring, but a relevant model has yet to be validated (Hausknecht et al 2005;Mothes et al 1996; Thomas et al 1998;Torres and Zimmerberg 1992). A specific group of brain regions that appear to be involved in ADHD (the cortex, striatum, and cerebellum) are sensitive to the toxic effects of alcohol administered during the fetoembryonic period (Astley et al 2009;Riikonen et al 1999Riikonen et al , 2005.…”
Section: Introductionmentioning
confidence: 89%
“…Results from both human and animal studies have suggested that dysfunctions of the mesolimbic/cortical dopaminergic (DA) system, which originates in the ventral tegmental area (VTA) may contribute to attention deficit/hyperactivity disorder (Denney, 2001;Greenhill et al, 2002;Davids et al, 2003). Impaired attention (Hausknecht et al, 2005) and dysfunctions of the mesolimbic/ cortical DA system are also observed in rats with prenatal ethanol exposure. Therefore, prenatal ethanol-exposed rats are a feasible animal model to study the neural mechanism of attention problems in individuals with FASDs.…”
mentioning
confidence: 99%
“…Rats received fetal alcohol exposure displays ADHD-like symptoms similar to human fetal alcohol syndrome (Hausknecht et al, 2005). It is assumed that dopamine transmission is impaired in this model of ADHD.…”
Section: In Utero Exposure To Alcoholmentioning
confidence: 99%